Desymmetrization strategy to achieve triptycene-based 3,6-dimethoxytriphenylenes via oxidative cyclodehydrogenation [data] - Reinhard, Dennis; Rominger, Frank; Mastalerz, Michael (Universität, 2022)
To achieve a highly symmetric triptycene based hexamethoxytriphenylene in high yield of 97 %, a less symmetric triptycene (C3v) is necessary as pre...
Gesehen am 09.02.2022
Keywords: Forschungsdaten; Datenbank